Teaching Cell to 6th Grade Students with Visual Impairment - Yazici, Fatih; Sozbilir, Mustafa (Egitim ve Bilim, 2020)
In this study, the design process of a model for the teaching of science concepts related to the ‘cell’ subject in 6th grade students with visual impairment (SVI) was discussed and the effectiveness of this design was evaluated from various aspects. Design Based Research method was used in this research which is based on ADDIE model for instructional design. In the first stage of the three-stage instructional design, the individual learning needs of the six SVI and their levels of learning the basic concepts in the ‘cell’ subject were determined. In the second stage, the teaching materials and activities were designed in accordance with the determined needs and the designed teaching model was tested on nine SVI in 6th grade. In the last stage, the instructional design was evaluated in terms of applicability, usefulness and contribution to concept learning. Semi-structured observation and interview forms were used as data collection tools and the obtained qualitative data were analyzed by using descriptive analysis approach. As a result of the study, it was determined that the teaching model designed in accordance with the determined needs contribute the students to learn the concepts of ‘Cell’ subject effectively and to reach the related acquirements. Bu çalışmada; görme engelli 6. sınıf öğrencilerine, Fen Bilimleri dersindeki ‘Hücre’ konusuna ait fen kavramlarının öğretimine yönelik bir modelin tasarım süreci ve tasarımın etkililiği değerlendirilmiştir. Öğretim tasarımı için ADDIE modelinin esas alındığı bu araştırma Tasarım Tabanlı Araştırma (TTA) yöntemi ile gerçekleştirilmiştir. Üç aşamalı öğretim tasarımının ilk aşamasında, görme engelli altı öğrencinin fene (Fen Bilimleri dersine) yönelik bireysel öğrenme ihtiyaçları ile ‘Hücre’ konusunda yer alan temel kavramları öğrenme düzeyleri belirlenmiştir. İkinci aşamada ise belirlenen ihtiyaçlar doğrultusunda öğretim materyalleri ve etkinlikleri tasarlanmış ve tasarlanan bu öğretim modeli 6. sınıfta öğrenim gören görme engelli dokuz öğrenciyle denenmiştir. Son aşamada ise tasarlanan öğretim modelinin uygulanabilirliği, kullanışlılığı ve kavram öğrenimine katkıları açısından değerlendirmesi yapılmıştır. Veri toplama araçları olarak yarı yapılandırılmış gözlem ve görüşme formları kullanılmış, elde edilen nitel veriler betimsel analiz yaklaşımı izlenerek çözümlenmiştir. Araştırma sonucunda belirlenen ihtiyaçları gidermeye yönelik ortaya koyulan tasarımın, ‘Hücre’ konusuna ait kavramların öğrenciler tarafından etkili bir şekilde öğrenilmesine ve ilgili kazanımlara ulaşılmasına katkı sağladığı belirlenmiştir.